EFFECT OF COMPACTION ON THE BEHAVIOUR OF KIRKUK GYPSEOUS SOIL (Journal of Engineering, 2006)
The purpose of the present work is to investigate the effect of compaction on the behaviour of gypseous soil. A testing program carried out to study the geotechnical properties and the behaviour of gypseous soil (gypsum content = 37% & 56%) taken from Kirkuk city. The tests include classification tests, chemical tests, X-ray diffraction analysis, compaction characteristics, compressibility & collapsibility, California Bearing Ratio (CBR) & shear strength tests.The effect of dry unit weight, water content, compactive efforts, relative compaction & soaking on the engineering properties of the soil tested are included in the program. All tests were carried out using Standard and Modified Proctor.Based on the results, several conclusions have been obtained. The soil compacted at the dry side of optimum tends to collapse upon soaking while the soil compacted at the wet side of optimum tends to swell . The percent of swelling for soil with =37% is more than that with =56%.Through the observation of shear strength test results, for the two compactive efforts and the two types of gypseous soil,the cohesion(c) increases with decreasing gypsum contents.The angle of internal friction () decreases with increasing moulding water content and increases with increasing gypsum contents.The soaked CBR values increase with increasing compactive efforts and gypsum content.